2021
DOI: 10.21873/anticanres.14812
|View full text |Cite
|
Sign up to set email alerts
|

TissueRNFT2Expression Levels Are Associated With Peritoneal Recurrence and Poor Prognosis in Gastric Cancer

Abstract: Background/Aim: Disease recurrence is frequently observed after curative resection of advanced gastric cancer resulting in a poor prognosis. In the present study, we identified a candidate biomarker to predict recurrence and prognosis after curative resection of gastric cancer. Materials and Methods: A transcriptome analysis was conducted using surgically resected cancerous tissue from patients with metastatic gastric cancer to identify genes that are upregulated in primary and metastatic tissues. Results: Rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…S3b), but not in BORIS-negative cells. Similar to NOS3 gene, RNTFT2 expression is associated with poor prognosis in cancer [ 55 ]. The full list of genes with intronic TSSs is presented in Additional file 3 : Table S2c.…”
Section: Resultsmentioning
confidence: 99%
“…S3b), but not in BORIS-negative cells. Similar to NOS3 gene, RNTFT2 expression is associated with poor prognosis in cancer [ 55 ]. The full list of genes with intronic TSSs is presented in Additional file 3 : Table S2c.…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that RNFT2 could inhibit inflammation response via influencing ubiquitination of IL-3Ra [ 34 ]. In the oncology field, the expression of RNFT2 in gastric cancer tissues was found positively associated with poor prognosis and high recurrence rates [ 35 ]. While in BCa, the function of RNFT2 had not been studied before.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies on the roles of RNFT2 in cancer research is relatively rare. A recent study demonstrated that tissue RNFT2 expression levels are associated with peritoneal recurrence and poor prognosis in GC 31 . Taken together, our results and other related findings suggest that the five upregulated genes mentioned above could be potential targets for GC research.…”
Section: Discussionmentioning
confidence: 99%